Contamination of skin and surfaces by cobalt in the hard metal industry - Kettelarij, Jolinde; Midander, Klara; Lidén, Carola; Julander, Anneli (Contact dermatitis, 2018)
Background It is well known that hard metal workers have historically been affected by contact allergy to cobalt. Knowledge is sparse about occupational skin exposure to cobalt, in terms of skin doses and sources of exposure, which could be used to improve protection of workers. Objectives To improve knowledge about skin doses and sources of skin exposure to cobalt within hard metal production, thereby facilitating better protection of workers. Methods Forty workers were sampled on the index finger by acid wipe sampling after 2 hours of work. The samples were analysed with inductively coupled plasma mass spectrometry. Cobalt spot testing was performed in the work environment. Results The highest skin doses were found among raw material workers. Skin doses among other production workers were also significant. Most office workers had low, but measurable, levels of cobalt on the skin. Glove use varied between workers. Cobalt was found on production equipment, on items in the canteen area, and on handles and buttons throughout the company. Conclusions Cobalt skin doses were prominent, and originated from contact with raw materials, sintered materials, and contaminated surfaces. Cobalt was present on surfaces outside production areas. Companies need to identify and reduce skin exposure for protection of workers.